Pengembangan Model Daur Ulang Sampah Plastik Dalam Jaringan Sistem Reverse Logistics - Suryana, Hendy (Universitas Suryakancana, 2019)
Abstract-The development of a plastic waste recycling model in the reverse logistics network system is based on the current plastic waste management business activities in Indonesia (in this case the Bekasi and surrounding areas), which is strengthened by some literature on the same business activities in several other countries, such as India. The reverse logistics system in Indonesia is currently one of the best alternatives that can be considered in reducing the limitations of raw material resources. In addition, reverse logistics is proven to provide economic value for business people, then environmental issues become one of the strongest motivations in conducting reverse logistics business. This study aims to develop a model of plastic waste recycling in Indonesia, specifically plastic waste of the compound type LDPE (Low Density Polyethylene) and HDPE (High Density Polyethylene) in the reverse logistics network system and to determine the distribution and transportation network system related to business management activities the plastic garbage. The development of this model can be developed based on empirical data in observing the behavior and characteristics of model variables. The results of the model can produce the total cost of a reverse logistics system in managing plastic waste in Bekasi and its surroundings at Rp. 196,220,250Abstrak-Pengembangan model daur ulang sampah plastik dalam sistem jaringan reverse logistics didasarkan pada aktivitas bisnis pengelolaan sampah plastik di Indonesia (dalam hal ini wilayah Bekasi dan sekitarnya) saat ini, yang diperkuat dengan beberapa literatur mengenai aktivitas bisnis yang sama di beberapa negara lain, seperti India. Sistem reverse logistics di Indonesia, saat ini menjadi salah satu alternatif terbaik yang dapat dipertimbangkan dalam mengurangi keterbatasan sumber daya bahan baku. Selain itu, reverse logistics terbukti dapat memberikan nilai ekonomis bagi para pelaku bisnis, lalu isu lingkungan menjadi salah satu motivasi terkuat dalam melakukan bisnis reverse logistics. Penelitian ini bertujuan untuk mengembangkan model daur ulang sampah plastik di Indonesia, khususnya sampah plastik berjenis senyawa LDPE (Low Density Polyethylene) dan HDPE (High Density Polyethylene) dalam sistem jaringan reverse logistics serta untuk menentukan system jaringan distribusi dan transportasi yang terkait dengan aktivitas bisnis pengelolaan sampah plastik tersebut. Pengembangan model ini dapat dikembangkan berdasarkan data empiris dalam mengamati perilaku dan karakteristik variabel-variabel model. Hasil model dapat dihasilkan total biaya sistem reverse logistics dalam pengelolaan sampah plastik di Bekasi dan sekitarnya sebesar Rp. 196,220,250,-.